Japanese genome‐wide association study identifies a significant colorectal cancer susceptibility locus at chromosome 10p14. Issue 11 (26th September 2017) - Takahashi, Yusuke; Sugimachi, Keishi; Yamamoto, Ken; Niida, Atsushi; Shimamura, Teppei; Sato, Tetsuya; Watanabe, Masahiko; Tanaka, Junichi; Kudo, Shinei; Sugihara, Kenichi; Hase, Kazuo; Kusunoki, Masato; et al.
Abstract : Genome‐wide association studies are a powerful tool for searching for disease susceptibility loci. Several studies identifying single nucleotide polymorphisms (SNP) connected intimately to the onset of colorectal cancer (CRC) have been published, but there are few reports of genome‐wide association studies in Japan. To identify genetic variants that modify the risk of CRC oncogenesis, especially in the Japanese population, we performed a multi‐stage genome‐wide association study using a large number of samples: 1846 CRC cases and 2675 controls. We identified 4 SNP (rs7912831, rs4749812, rs7898455 and rs10905453) in chromosome region 10p14 associated with CRC; however, there are no coding or non‐coding genes within this region of fairly extensive linkage disequilibrium (a 500‐kb block) on 10p14. Our study revealed that the 10p14 locus is significantly correlated with susceptibility to CRC in the Japanese population, in accordance with the results of multiple studies in other races. Abstract : We conducted a new genome‐wide association study with 1, 846 Japanese colorectal cancer cases and 2675 controls. We identified four SNPs (rs7912831, rs4749812, rs7898455, and rs10905453) in chromosome region 10p14 associated with colorectal cancer in Japanese patients.